Review of White-box Implementations of AES Block Cipher and Known Attacks - Martun M. Karapetyan (Изд-во НАН РА)
Conventional encryption algorithms are designed to be secure in the "black-box" context, i.e. the attacker has access to the input and output of the algorithm, but cannot observe the intermediate values generated during the software execution. Yet in some cases, the encryption algorithm runs in a hostile environment, where the attacker can see not only the input and output values but also has full access to all the internal values and can change the execution at will.
Keywords: Mathematics; Algorithm